The Intimacy with Muzakki in Increasing Trust, Commitment and Loyalty to Increase ZISWAF Fund at Zakah Institutions - Soleh, Mochammad; Linggasari, Yasinta Suci (Universitas Airlangga, 2023)
Abstract This study aims to determine the effect of the intimacy of zakat institutions with muzakki in order to gain trust, commitment and loyalty in order to encourage an increase in charitable funds, namely Zakat, Infaq and Sadaqah (ZIS). This study uses a quantitative approach through the Partial Least Square (PLS) method on 132 muzakki permanent members of zakat institutions using the variables of familiarity, trust, commitment, and loyalty. The results of this study note that the closeness of the relational relationship between zakat institution officials and muzakki as assessed from the familiarity factor in general has a positive relationship with the emergence of trust and commitment which in turn fosters muzakki's loyalty to the zakat institution they choose; However, this closeness does not significantly influence the emergence of trust, commitment and loyalty. One of the reasons for this to happen is that the public still has high distrust of zakat institutions, so it is very important for zakat institutions to start using a professional and responsible management pattern and have the support of all people. Keyword: Intimacy, Trust, Commitment, and Loyalty Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh keakraban lembaga zakat dengan muzakki guna mendapatkan kepercayaan, komitmen dan loyalitas agar mendorong peningkatan dana amal yaitu Zakat, Infaq dan Shadaqah (ZIS). Penelitian ini menggunakan pendekatan kuantitatif melalui metode Partial Least Square (PLS) pada 132 muzakki anggota tetap lembaga zakat dengan menggunakan variable keakraban , kepercayaan, komitmen, dan loyalitas. Hasil penelitian ini diketahui bahwa keeratan hubungan relasional antara petugas lembaga zakat dan muzakki yang dinilai dari faktor keakraban secara umum memiliki hubungan yang positif dengan timbulnya kepercayaan dan komitmen yang pada akhirnya menumbuhkan loyalitas muzakki pada lembaga zakat yang mereka pilih; akan tetapi keeratan tersebut tidak berpengaruh secara signifikan terhadap munculnya kepercayaan, komitmen dan loyalitas. Salah satu sebab hal tersebut terjadi adalah masih tingginya ketidakpercayaan masyarakat terhadap lembaga zakat sehingga sangat penting bagi lembaga zakat untuk mulai menggunakan pola manajemen yang profesional dan bertanggung jawab serta mendapat dukungan dari semua umat. Kata Kunci: Keakraban, Kepercayaan, Komitmen, dan Loyalitas